Produksi Oligomer Kitosan dari Limbah Udang Windu (Panaeus monodon) Menggunakan Enzim Kitosanase dari Isolat Bakteri Klebsiella sp. - Sarni, Sarni; Natsir, Hasnah; Dali, Seniwati (Indonesian Journal of Chemical Research, 2016)
Chitosan is a biopolymer that is the main content of D-glucosamine and several parts of N-acetyl-D-glucosamine bound to Î²- (1-4) glucoside. Chitosan receive special attention as functional biopolymers for applications in various fields. Chitosan is more effectively absorbed into the human body when it gets converted into chitosan oligomer form. Chitosan oligomer is a mixture of oligomers of D-glucosamine are formed through a process of severing ties depolymerization of chitosan with Î²-glycosidic. This study aims to produce chitosan oligomer of waste tiger shrimp (Penaeus monodon) using enzyme kitosanase of bacteria Klebsiella sp. Chitosan oligomer produced by using the enzyme chitosanase at a temperature of 40 Â°C and pH 8 with the activity of 0.309 U/mL (5,235 U/mg) obtained in the form of a mixture of monomer to octamer, which soluble in acetic acid 0.25% to 0.5%, having intrinsic viscosity decreases with increasing time of incubation is 0.195 (1 hour incubation); 0.9 (incubation 2 hours) and 0.7 (incubation 3 hours) with molecular weight range of 4103.12 g/mol (incubation 1 hour) ; 1483.48 g/mol (incubation 2 hours) and 1065.79 g/mol (incubation 3 hours).